Perlindungan Hukum Terhadap Wanprestasi dalam Sewa Menyewa dengan Pejabat Pemerintah yang Diganti" (Studi Kasus PN Kutai Barat No. 56/Pdt.G/2020) - Seiff, Fariz; Lukman, FX Arsin (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
In the lease agreement, it can be understood that where one party binds himself to give enjoyment of an item to another party, for a certain time with payment that the party can afford. The problem raised in this case is that the tenant is an official representing a government agency who does not pay the rent even though the deed of the lease agreement has been signed, then when the achievement has not been fulfilled, the official has been replaced. What will be discussed in this article is the responsibility for fulfilling the achievements of the Mahakam Ulu District Government. To answer these problems, normative juridical research methods are used. , this study did not use observations or interviews with respondents. When viewed from the angle of its shape, this research is a prescriptive research. Prescriptive research is research that aims to provide solutions or suggestions in overcoming a problem. First, it will discuss how the plaintiff's lawsuit does not include the Regent of Ulu Regency as the Defendant in the lease agreement, then an analysis will be carried out regarding legal protection against those who rent out defaults carried out by the Public Works and Public Housing Agency.